Transformasi keunggulan kompetitif industri pangan halal: Tinjauan sistematis pengaruh sertifikasi halal terhadap nilai jual dan diferensiasi produk - Sri Utami; Ambarwati Akib; Dwi Utami; Magfirah Wahyu Ramadhani; Nurul Chalisa Majiding (Journal of Halal Industry Studies, 2025)
The global halal food market is experiencing significant growth, with a valuation of USD 2.71 trillion in 2024, driven by the implementation of mandatory halal certification regulations in Indonesia, which is transforming the food industry's competitive landscape. This research aims to analyze the influence of halal certification on product value and food product differentiation through a Systematic Literature Review approach. The research method employs the PRISMA framework, analyzing 10 reputable international journals published during 2021-2025 across the Scopus, Web of Science, ScienceDirect, and Google Scholar databases. Thematic analysis identifies patterns and mechanisms of halal certification's influence on market performance. Research findings demonstrate that halal certification increases Muslim consumers' willingness to pay, serves as a quality signal that enhances brand value, and creates a sustainable competitive advantage through blockchain integration to enhance supply chain transparency. Product differentiation is strengthened by multidimensional strategies encompassing price differentiation, nutritional quality, packaging innovation, and ingredient authenticity. Research concludes that halal certification constitutes a strategic asset, creating sustainable added value, and offers recommendations for halal standard harmonization, IoT and blockchain technology adoption, and the development of a comprehensive differentiation strategy for food producers.